ولاء الموالاة في الفقه الإسلامي ومشكلات المؤلفة قلوبهم في ماليزيا - نور خطية بنت دول منير (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
This study focuses on the issue of contract of guardianship (wala’ al-muwalat) in the Islamic Jurisprudence and the problems of Muslim converts in Malaysia. The study proposes the method of reconciling the difference through piecing together the evidences (talfiq) in solving the problems. It presents opinions and evidences of Muslim jurists in discussing the issue of wala’ al-muwalat, as well as the issue of talfiq and how they can be implemented in Malaysia. The study has adopted the method and approach of the jurist in discussing the issue and explaining the positions of the different schools of law since only the Hanafiyyah holds the position of the wala’ al-muwalat. The researcher subscribes to the opinion of Hanafi on this issue and attempts to show the significance of implementing the wala’ in accordance with the interests and necessities of Muslim converts. The study provides approaches to problems faced by Muslim converts in Malaysia by focusing on their social, economic and the problems of Islamic education as well as their problems in practicing Islam. The study concludes by reiterating that wala’ al-muwalat through talfiq is the most practical way to help alleviate the problems faced by Muslim converts in Malaysia.